(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The aims: To determine the effect of some chemical materials on the water powder ratio of dental stone. Material and Methods: Three types of chemical materials (rosin, nigella stavia oil and sodium lauryl sulfate) were incorporated into three kinds of type III dental stone (Zeta, Elite and Dental stone) at four concentrations (0.5%, 1%, 1.5% and 2%). The collected data of water powder ratio were subjected to the descriptive analysis (mean and stander deviation), student T test (to evaluate the difference between standard and experimental groups) and one-way analysis of variance (ANOVA) (to show if there are significant differences among experimental groups). Results: Revealed that the incorporation of these chemical materials into each type of dental stone resulted in changing their evaluated water powder ratio; this change varies with the type, concentration of the added chemical material and type of dental stone being used. Conclusion: The most pronounced effect of the chemical additives that used in this study on the water powder ratio of the experimental dental stones was achieved with the addition of sodium lauryl sulfate.